2014
DOI: 10.1515/pac-2014-0716
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of lipases for estolides synthesis

Abstract: Lipase-catalyzed synthesis of estolides starting from different saturated (C16 16OH, C18 12OH) and unsaturated (C18:1 9 cis 12-OH) hydroxy-fatty acids was investigated. For this reason, the catalytic efficiency of several native and immobilized lipases in different organic reaction media at temperatures up to 75 °C was studied. The formation of mono-and di-lactone as well as estolide's chain elongation depends on the type and source of lipase. The lipase from Pseudomonas stutzeri immobilized by cross-linking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…To the best of our knowledge, this is the first report about the biocatalytic copolymerization of ECL and HFAs. Three of the selected HFAs, specifically 16HHDA, 12HSA, and RCA, have been used in our previous study as substrates for the synthesis of estolides (homopolymers of HFA) catalyzed by lipases, but not for copolymers. Although the enzymatic synthesis of 10‐hydroxystearic acid (10HSA), starting from oleic acid and oleate hydratase from different sources was reported by several groups, 10HSA based polyester synthesis and characterization was not yet accomplished.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first report about the biocatalytic copolymerization of ECL and HFAs. Three of the selected HFAs, specifically 16HHDA, 12HSA, and RCA, have been used in our previous study as substrates for the synthesis of estolides (homopolymers of HFA) catalyzed by lipases, but not for copolymers. Although the enzymatic synthesis of 10‐hydroxystearic acid (10HSA), starting from oleic acid and oleate hydratase from different sources was reported by several groups, 10HSA based polyester synthesis and characterization was not yet accomplished.…”
Section: Resultsmentioning
confidence: 99%
“…The biocatalyst with the best catalytic efficiency for the synthesis of the targeted copolymers was selected by screening four commercially available immobilized lipases: Novozym 435 (from Candida antarctica B), Lipozyme TL (from Thermomyces lanuginosus ), as well as two CLEA Pseudomonas stutzeri lipases (one specific for organic media and one with general applicability). Additionally, the native lipase from Pseudomonas fluorescens was also tested, based on our previous study which proved it as the best‐performing biocatalyst for estolides synthesis . The conversions were monitored by GC‐MS analysis, using hexadecane as internal standard.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martin‐Arjol et al () synthesized 10(S)‐hydroxy‐8(E)‐octadecenoic acid mono‐estolides with Novozym 435 catalyst and obtained a maximum of 30% yield. Todea et al () synthesized estolides from 16 and 18 hydroxy fatty acids using several native immobilized lipases and obtained estolides with a degree of polymerization of up to 10 and a conversion of greater than 80%.…”
Section: Synthesis Of Fatty Acid Estolidesmentioning
confidence: 99%
“…It is concluded that the selectivity of lipases was strongly dependent on the position of the hydroxyl group in the hydroxy fatty acid chain, slightly on the hydroxy acid chain length, and on lipase concentration. Hayes and Kleiman (1995) Todea et al (2015) synthesized estolides from 16 and 18 hydroxy fatty acids using several native immobilized lipases and obtained estolides with a degree of polymerization of up to 10 and a conversion of greater than 80%.…”
Section: Lipasesmentioning
confidence: 99%